Effect of Curcumin Nanoemulsion on Insulin Levels and Malondialdehyde Concentration in Zebrafish Embryos Model of Gestational Diabetes Mellitus - Subandi, Subandi; Paramita, Galuh Anggarda; Khoir, Safa’atul; Nurdiana, Nurdiana; Wiyasa, I Wayan Arsana (Prodi Kedokteran Fakultas Kedokteran Universitas Malahayati, 2025)
Gestational Diabetes (GD) is a condition characterized by increased blood sugar levels (hyperglycemia) in pregnant women who were previously undiagnosed with diabetes. Hyperglycemia disrupts the performance of pancreatic β cells that are responsible for producing the hormone insulin. Curcumin functions as an anti-inflammatory, allowing the insulin reaction to occur more quickly and insulin production to increase. Methods. Post Test Only Control Group Design was used in this experimental study which was tested on each research variable consisting of 1000 zebrafish embryos divided into 5 treatment groups with each sample containing 40 embryos, consisting of a negative control, a positive control exposed to 3% glucose, and a diabetic group given curcumin nanoemulsion with three different doses (0.3125 μg/ml, 0.625 μg/ml, 1.25 μg/ml). The exposure was carried out at 2-50 hpf and then measured using INS ELISA Kit and MDA ELISA Kit. The results were analyzed using a one-way ANOVA test. Results. NOVA showed p = 0.254 for insulin levels (not significant) and p = 0.029 for MDA concentrations. Post-hoc analysis revealed that the significant difference occurred only between the negative (K−) and positive (K+) control groups (p = 0.012), while the curcumin-treated groups (K1, K2, K3) showed no statistically significant differences compared with either control group (p > 0.05). Conclusion. Curcumin nanoemulsion tended to increase insulin levels and reduce MDA concentrations, but these effects were not statistically significant (p > 0.05). The induction of hyperglycemia with 3% glucose successfully established oxidative stress in zebrafish embryos, validating the model. Further studies with larger sample sizes and molecular analyses are needed to confirm the biological trends observed.